North – southern asymmetry of magnetic field variations distribution during storm on the 4/6/2000 on AIA meridian - O. I. Maximenko; V. G. Bakhmutov; G. V. Melnyk; O. Ja. Shenderovska (Ukrainian Antarctic Journal, 2010)
By model calculations (Tsyganenko's Т01 model) during magnetic storm on April, 6th 2000 characteristics of north – southern asymmetry of global and Earth surface distribution of magnetic disturbances fields, an arrangement of observatory AIA and its conjugate point, and also their secular changes from 1990 to 2011 are defined.